The Influence of Inclusive Leadership on Teacher Performance through Educational Quality Management as an Intervening Variable - Muhammad Irfan Z.A; Arik Susbiyani; Amalina Maryam Zakkiyah (Utan Kayu Publishing, 2025)
Education is considered as an aspect that plays a crucial role in preparing and shaping a future generation of young people who are resilient, have character, are independent, and competitive. Teachers are required to have performance that is able to provide and realize the hopes and desires of all in achieving good quality education. This study aims to analyze the effect of inclusive leadership on education quality management and teacher performance, and to analyze the effect of inclusive leadership on teacher performance through intervening education quality management. This study uses descriptive and verification methods with a quantitative approach. The data for this study are primary data obtained through questionnaire distribution. The population in this study were all elementary school teachers in the Eastern Region of Jember Regency. The number of samples was determined at 200 respondents. Sampling was carried out using proportional random sampling. Data analysis used Structural Equation Modeling (SEM) analysis with the help of WarpPLS software. The research findings indicate that inclusive leadership significantly influences educational quality management. Inclusive leadership significantly effect on teacher performance. Educational quality management significantly effect on teacher performance. Inclusive leadership significantly effect on employee performance, with intervening educational quality management. The research findings show that educational quality management role as an intervening variable.